Gonadotrophins or clomiphene citrate in women with normogonadotropic anovulation and CC failure: does the endometrium matter?. Issue 6 (2nd June 2020) - Bordewijk, E M; Weiss, N S; Nahuis, M J; Kwee, J; Lambeek, A F; van Unnik, G A; Vrouenraets, F P J; Cohlen, B J; van de Laar-van Asseldonk, T A M; Lambalk, C B; Goddijn, M; Hompes, P G; et al.
Abstract: STUDY QUESTION: Is endometrial thickness (EMT) a biomarker to select between women who should switch to gonadotropins and those who could continue clomiphene citrate (CC) after six failed ovulatory cycles? SUMMARY ANSWER: Using a cut-off of 7 mm for EMT, we can distinguish between women who are better off switching to gonadotropins and those who could continue CC after six earlier failed ovulatory CC cycles. WHAT IS ALREADY KNOWN: For women with normogonadotropic anovulation, CC has been a long-standing first-line treatment in conjunction with intercourse or intrauterine insemination (IUI). We recently showed that a switch to gonadotropins increases the chance of live birth by 11% in these women over continued treatment with CC after six failed ovulatory cycles, at a cost of €15 258 per additional live birth. It is unclear whether EMT can be used to identify women who can continue on CC with similar live birth rates without the extra costs of gonadotropins. STUDY DESIGN, SIZE, DURATION: Between 8 December 2008 and 16 December 2015, 666 women with CC failure were randomly assigned to receive an additional six cycles with a change to gonadotropins ( n  = 331) or an additional six cycles continuing with CC ( n  = 335), both in conjunction with intercourse or IUI. The primary outcome was conception leading to live birth within 8 months after randomisation. EMT was measured mid-cycle before randomisation during their sixth ovulatory CC cycle. The EMT was available in 380 women, of whom 190 were allocated to gonadotropins and 190 were allocated to CC. PARTICIPANTS/MATERIALS, SETTING, METHODS: EMT was determined in the sixth CC cycle prior to randomisation. We tested for interaction of EMT with the treatment effect using logistic regression. We performed a spline analysis to evaluate the association of EMT with chance to pregnancy leading to a live birth in the next cycles and to determine the best cut-off point. On the basis of the resulting cut-off point, we calculated the relative risk and 95% CI of live birth for gonadotropins versus CC at EMT values below and above this cut-off point. Finally, we calculated incremental cost-effectiveness ratios (ICER). MAIN RESULTS AND THE ROLE OF CHANCE: Mid-cycle EMT in the sixth cycle interacted with treatment effect ( P  < 0.01). Spline analyses showed a cut-off point of 7 mm. There were 162 women (45%) who had an EMT ≤ 7 mm in the sixth ovulatory cycle and 218 women (55%) who had an EMT > 7 mm. Among the women with EMT ≤ 7 mm, gonadotropins resulted in a live birth in 44 of 79 women (56%), while CC resulted in a live birth in 28 of 83 women (34%) (RR 1.57, 95% CI 1.13–2.19). Per additional live birth with gonadotropins, the ICER was €9709 (95% CI: €5117 to €25 302). Among the women with EMT > 7 mm, gonadotropins resulted in a live birth in 53 of 111 women (48%) while CC resulted in a live birth in 52 of 107 women (49%) (RR 0.98, 95% CI 0.75–1.29). LIMITATIONS, REASONS FOR CAUTION: This was a post hoc analysis of a randomised controlled trial (RCT) and therefore mid-cycle EMT measurements before randomisation during their sixth ovulatory CC cycle were not available for all included women. WIDER IMPLICATIONS OF THE FINDINGS: In women with six failed ovulatory cycles on CC and an EMT ≤ 7 mm in the sixth cycle, we advise switching to gonadotropins, since it improves live birth rate over continuing treatment with CC at an extra cost of €9709 to achieve one additional live birth. If the EMT > 7 mm, we advise to continue treatment with CC, since live birth rates are similar to those with gonadotropins, without the extra costs. STUDY FUNDING/COMPETING INTEREST(S): The original MOVIN trial received funding from the Dutch Organization for Health Research and Development (ZonMw number: 80-82310-97-12067). C.B.L.A. reports unrestricted grant support from Merck and Ferring. B.W.M. is supported by a NHMRC Practitioner Fellowship (GNT1082548) and reports consultancy for Merck, ObsEva, IGENOMIX and Guerbet. All other authors have nothing to declare. TRIAL REGISTRATION NUMBER: Netherlands Trial Register, number NTR1449